« Prince Posterity [...] is generally just to us scribblers » (Jane West) : Femmes de lettres, oubli genré et matrimoine dans les livres de conduite britanniques (1760-1820) - Paul Lazaro Perez (XVII-XVIII)
In the late eighteenth century, conduct books mostly targeted women and were often produced by female literary celebrities. Yet, despite diverse ideological leanings, these women frequently failed to promote the cultural and historical legacies of other women, and sometimes worked to obscure their contributions to their readership. This article offers a brief overview of this phenomenon. First, it provides context on conduct literature, which could have aided the transmission of women’s cultural legacy owing to specific assets. Then, it examines the processes that played a part in the historical and cultural erasure of women in conduct manuals : both passive and active forms of ignorance construction. This leads to a final analysis of strategies of identity formation in female conduct book writers, which often drive their neglect or hostility toward cultural and historical material left by other women, with disastrous results on their own legacy in a reactionary cultural context.